Place-based post graduate education case analysis: Experiential learning at the work-place - Ma. Felma Carlos Tria; Leila R. Gano; Justinian Filoteo; Eva Imingan; Mary Jane Gonzales; Leny Dellosa (Universidade Estadual de Alagoas, 2024)
This research analyzed three (3) cases in the Institute of Graduate & Professional Studies (IGPS) at Universidad de Manila where place-based education (PBE) was realized at the place of work of post graduate students through experiential learning. In addition, actual experiences of executive scholars who underwent training at  the Asian Institute of Management (AIM) under the CHED-AIM program "Global Academic Leadership Program (GALP) for Local Universities and Colleges" (LUC) shared their experiences to give additional enlightenment on the impact of place-based education. Results underline the success impact of PBE to post graduate students' integration of principles, theories, skills, frameworks, and methodologies learned from the courses of the program and applied in the place of work.  Utilization of the PBE learning approach has proven to increase the academic achievement of students in their post-graduate studies. Two (2) models were formulated from results, both giving evidence of  the utilization and implementation of graduate students' own learning to the real-life experiences at the workplace, in response to and in alignment with  the United Nations Sustainable Development Goal (UNSDG) No. 4 (Quality Education)